2020
DOI: 10.1093/ehjcvp/pvaa097
|View full text |Cite
|
Sign up to set email alerts
|

Patient-reported outcomes and medication adherence in patients with heart failure

Abstract: Aim Patient-reported outcome measures (PROMs) may predict poor clinical outcome in patients with heart failure (HF). It remains unclear whether PROMs are associated with subsequent adherence to HF medication. We aimed to determine whether health-related quality of life, anxiety and depression were associated with long-term medication adherence in these patients. Methods and results A national cohort study of Danish patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
40
2
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(47 citation statements)
references
References 26 publications
3
40
2
2
Order By: Relevance
“…Data from these HF registries 17 21 revealed a lower prescription rate for all 3 categories of medications. However, recent prospective HFrEF trials showed a higher prescription rate for these medications 15 . In the present study, the use of renin-angiotensin system blockers was 91.5%, which included ARNIs (32.4%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Data from these HF registries 17 21 revealed a lower prescription rate for all 3 categories of medications. However, recent prospective HFrEF trials showed a higher prescription rate for these medications 15 . In the present study, the use of renin-angiotensin system blockers was 91.5%, which included ARNIs (32.4%).…”
Section: Discussionmentioning
confidence: 99%
“…PROs enable physicians to deliver more patient-centered care, thereby improving patients’ quality of life. A recent study showed that nonadherence to medication also correlated with poor PROs 15 . Real-world nationwide data on adherence to guideline-recommended treatment and PROs in Asian patients with HF are lacking with respect to ARNIs.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, mechanism(s) accounting for hospitalizations may not be specific to HF, but may also affect comorbidities. Potentially preventable nonspecific mechanisms could involve systemic responses such as inflammation, systemic stress responses, and increased symptom perception, poor adherence to diet or medications, or depression (13, 20, 40, 43).…”
Section: Discussionmentioning
confidence: 99%
“…Clinically anxious individuals have also been found to have higher levels of IL-6 [35] and lower levels of morning cortisol, even in the absence of depression [35]. Anxiety is associated with lesser performance of physical activity and lower educational levels, but unlike depression, has not been associated with decreased adherence to pharmacologic treatment [36], although anxious patients are less likely to be adherent to cardiac rehabilitation programs [37]. Anxiety is also associated with sleep disturbance, which may itself present a risk factor for poor outcomes in HF.…”
Section: Discussionmentioning
confidence: 99%